RANCANG BANGUN SISTEM PENDINGIN PELTIER DAN MONITORING SUHU PADA PANEL SURYA - Khalid, Muhamad; Nurussa’adah, n/a; Maulana, Eka (Jurnal Mahasiswa TEUB, 2024)
Solar energy as a sustainable renewable energy source has become a major focus in energy technology research and development. Solar panels that convert solar energy into electricity are important role in this energy transition. The performance of solar panels is measured through output parameters such as voltage and current, which are influenced by several factors, especially temperature. Every 1°C (from 25°C) increase will result in a decrease in power of 0.25% to 0.5%. Therefore, this research aims to design a peltier cooling system using the Thermoelectric Cooler TEC1-12706 to reduce the temperature of solar panels and increase the power produced. This system is equipped with an MLX90614 temperature sensor to monitor and limit the effect of cooling, and an INA219 current and voltage sensor to monitor panel performance. Data can be accessed in real time through the Blynk application. The study was conducted on December 13 – 18, 2024 at 10.00 WIB – 11.00 WIB at coordinates 7°57'03.8"S 112°37'41.4"E. The results showed that temperature measurements using the MLX90614 has an accuracy range of 99.70% to 99.94%. Meanwhile, current and voltage measurements using the INA219 has an accuracy range of 99.17% to 100% and 99.33% to 100%. The performance results of the Blynk application as a monitor function well by being able to display values and graphs of current, voltage, temperature, power and cooling indicators. This system has a power requirement of 44.37 W, with the highest temperature drop of 13.78%, the highest current increase of 7.69%, the highest voltage increase of 3.89%, and the highest power increase of 11.82% after using the peltier cooling system. However, the increase in power generated is not proportional to its power usage. Keywords: Solar panel, cooling system, Thermoelectric Cooler, MLX90614, INA219, Blynk.